EVALUASI PENGARUH SISTEM MANAJEMEN PENDIDIKAN DI SEKOLAH DASAR TERHADAP PENINGKATAN KREATIVITAS SISWA - Hanansya Nur Salsabilla,; Nanda Dwi Utami,; Nathania Alyfa Syahada,; Arita, Arita (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2024)
Education at the elementary level has an important role in shaping students' creativity, which is the key to success in facing future challenges. One factor that can influence student creativity is the education management system implemented in elementary schools. This research aims to evaluate the effect of the education management system in elementary schools on increasing student creativity. The research method used is an evaluation study with a quantitative approach. Data was collected through questionnaires distributed to elementary school students to measure their perceptions of the education management system implemented in schools. Apart from that, academic score data was also obtained to measure students' creativity levels. The research results show that there is a positive relationship between the education management system in elementary schools and increasing student creativity. Schools that implement an inclusive education management system, provide space for students' creative expression, and encourage project-based learning tend to have higher levels of student creativity. Based on these findings, it is recommended that elementary schools continue to improve the implementation of educational management systems that support the development of student creativity. This can be done through training for teachers in designing learning that promotes creativity, the use of innovative educational technology, and collaboration between schools, parents and communities to create learning environments that stimulate student creativity